IMPLEMENTAÇÃO DE EQUIPAMENTOS PARA AVALIAÇÃO DAS PROPRIEDADES REOLÓGICAS DO CONCRETO AUTOADENSÁVEL - Bohn, Tiago R.; Rambo, Dimas A. S.; Hermann, Thiana; Larssen, Catia; Duart, Marcelo (Salão do Conhecimento, 2013)
Resumo